KOMPETENSI GURU BIMBINGAN DAN KONSELING DAN UPAYA PEMBINAAN - Rafiqah, Tamama (Universitas Riau Kepulauan, 2013)
Problems of students at the school increasingly complex problems with the rapid development of world education. This requires counselor in the school have the skills and abilities in performing services Guidance and Counseling for students in schools. Ability and skill is evident from the competency of counselor. Thus, to achieve the necessary development and improvement of their competence. This study were aims at: (1) current counselor competence, (2) development efforts undertaken with respect to the principal counselor competence, (3) differences in counselor competence based accreditation of schools and (4) differences in counselor competence based on the length of service.This research used descriptive approach. The population of this research was the counselor in Senior High School at Rejang Lebong, amounting to 16 people. All counselor as sample. The instrument that had been used was close quesstionnaire by Likert scale model. Percentage technique was used to analized the first. Narative technique was used to analyzed the second research intended. t-test technique was used to analyzed the third and fourth research intended.The results of research are: (1) the general competence of counselor is currently quite good, (2) construction effort undertaken is of a general nature intended for all teachers in schools, (3) there are differences in counselor competence on school accreditation, although not significant, and (4) there are differences in counselor competence based on length of service, although not significantly. Given the results of this study are expected to carry out the duties counselor professionalism in schools refers to a predetermined standard of competence and to increase the principal's role in the provision of services on Guidance and Counseling in school.